Water Penetration of Concrete made with Coarse Aggregates from Demolishing Waste - Koondhar, M. F.; Memon, B. A.; Oad, M.; Chandio, F. A.; Chandio, S. A. (Engineering, Technology & Applied Science Research, 2020)
The results of laboratory investigations on water penetration in concrete made with coarse aggregates from demolishing waste are presented in this paper. Seven batches of standard size concrete cubes were cast with recycled aggregates from demolished concrete replacing coarse aggregates in percentages from 0% to 60%. The compressive strength of the samples was evaluated by non-destructive testing with the use of the Schimidz hammer. It was found that the strength reduces with an increase in recycled aggregate percentage. The maximum loss of strength due to the induction of recycled aggregates was 32% in the batch with 60%recycled aggregates. All samples were subject to constant water pressure of 5 bars for 72 hours. From the obtained results it was shown that the water penetration depth increases with increase in recycled aggregates rate. With 10% and 20% replacement the samples allowed less water to penetrate than conventional concrete samples, but 76% more penetration depth was recorded in samples with 60% replacement. Strength and water penetration results from dosages up to 20% show that the durability of the produced concrete allows it to be used in structural members with consideration of strength reduction in the design process. However, more water penetration with higher dosages of recycled aggregates needs proper care in design and usage of the concrete particularly for locations where concrete is exposed to water pressure.